Biomineralization-inspired dendrite-free Zn-electrode for long-term stable aqueous Zn-ion battery. (1st December 2022) - Zhang, Fan; Liao, Ting; Liu, Cong; Peng, Hong; Luo, Wei; Yang, Haoyu; Yan, Cheng; Sun, Ziqi
Abstract: Rechargeable aqueous Zn-ion batteries (AZIB) are a promising type of energy storage device but suffer from the growth of uncontrollable Zn dendrites, which result in the shortcut of the battery. Herein, inspired by the regulated nucleation and growth of inorganic minerals from porous organic matrix within the biomineralization process, dopamine derived N-doped carbon spheres with abundant gaps and voids are assembled onto the Zn metal anode (Zn@C) as an artificial solid electrolyte interphase (SEI) layer to modulate the nucleation and growth of a smooth Zn layer without dendrites and suppress the corrosion and hydrogen evolution side reactions. When assembled into Zn-ion batteries, the bioinspired electrode presents comprehensive enhancements in terms of capacity, rate performance, and stability. This unique design of electrode allows long-term stable cycling up to 2100 h at 5 mA cm −2 for a symmetric battery and gives rise to the performance of 315 mAh g −1 at 0.5 A g −2 and 95% retention of its original capacity after 1000 cycles for the Zn@C//V2 O5 pouch cell, which outperform most of reported Zn electrodes. The flexible pouch cells displace significant durability towards folding, bending, and piercing, demonstrating its capability for practical applications in wearable devices. Graphical Abstract: Biomineralization-inspired heterointerface provides a pre-organized nitrogen-doped carbon spheres artificial SEI layer to regulate the nucleation and growth of dendrite-free Zn and inhibit the corrosion and hydrogen evolution side reactions for long-term stable operation of aqueous Zn-ion batteries. ga1 Highlights: An artificial SEI layer by learning from the natural biomineralization process is constructed. The bioinspired SEI layer homogenizes the nucleation for uniform and dendrite-free Zn plating and suppresses the side reactions. The bioinspired electrode exhibits comprehensive enhancements in capacity, rate performance, and stability. The pouch cell delivers a capacity of 315 mAh g −1 at 0.5 A g −2 and 95% retaining after 1000 cycles.